Food security status of Suchana-participating households in north-eastern rural Bangladesh - Haque, Md Ahshanul; Choudhury, Nuzhat; Ahmed, S. M. Tanvir; Farzana, Fahmida Dil; Ali, Mohammad; Naz, Farina; Khan, Ashfaque; Wahid, Barbie Zaman; Siddiqua, Towfida Jahan; Akter, Rumana; Rahman, Sheikh Shahed; Faruque, A. S. G.; et al. (Frontiers in Public Health, 2022)
Despite achieving remarkable progress, food insecurity remains a major public health challenge in Bangladesh, and severe food insecurity status has not been reduced in susceptible areas and vulnerable regions in Bangladesh. Wetlands that are susceptible to flooding can be found in Bangladesh's north-eastern Sylhet division. Suchana, a large-scale nutrition programme, implemented nutrition-specific and sensitive interventions in poor and very poor households in Sylhet and Moulvibazar districts in the north-eastern region of Bangladesh. The aim of this article is to assess the association between the Suchana intervention and household food security status among poor and very poor households in north-eastern rural Bangladesh using the Suchana baseline and endline survey databases. The baseline survey was conducted between November 2016 and February 2017, while the endline survey was undertaken 3 years later, during the same months. The outcome variable in this analysis was household food security status, which was measured using the Food and Nutrition Technical Assistance's Guideline. Descriptive statistics were used to summarize the data; after controlling for the union as a cluster and relevant covariates, a multiple multinomial logistic regression model was used to estimate the independent effect of the Suchana intervention as an exposure. Overall, 14.0% of households were food secure at the baseline survey (intervention: 14.1%, control: 14.0%) and 22.0% were food secure (intervention: 26.6%, control: 20.2%) at the endline survey. For households in the intervention area in comparison to the control area, the odds of being moderately food insecure [aOR: 1.36 (1.05, 1.76), p < 0.05], mildly food insecure [aOR: 1.83 (1.33, 2.51), p < 0.001], or food secure [aOR: 2.21 (1.47, 3.33), p < 0.001] compared to being severely food insecure was significantly higher. Thus, we infer that the 3 years of Suchana intervention marginally increased household food security status among the socio-economically disadvantaged population in north-eastern rural Bangladesh. If concerns regarding gender equity, women's education, and income-generating activities are addressed, the population could experience even greater benefits in food security. In order to overcome these challenges, all stakeholders including programme implementers and policymakers should work together to implement the appropriate measures.